Lessons from co-impacts assessment under the Mitigation Action Plans and Scenarios (MAPS) Programme. (17th November 2017) - Cohen, Brett; Tyler, Emily; Torres Gunfaus, Marta
Abstract : The MAPS Programme has been active in Brazil, Chile, Colombia and Peru in supporting the development of an evidence base to inform the processes involved in climate mitigation policy-making. The programme combines detailed quantitative analysis with an extensive stakeholder engagement process to provide policy and decision makers with the information required for long-term climate mitigation planning. In recognition of the critical need to consider the developmental context and agenda in climate policy-making, the projects undertaken in these countries have experimented with various types of assessments of developmental impacts at both the macro and micro levels. These impacts have been collectively termed co-impacts to reflect the fact that these may be either positive or negative. In this article the value and challenges associated with co-impacts work for climate mitigation policy are considered. The value of including co-impacts analysis in the MAPS processes included increased stakeholder buy-in, making the case for mitigation action, informing INDCs and the prioritization of particular mitigation actions. Challenges include those associated with obtaining locally relevant data, the selection and operation of appropriate macro-economic models and analytical approaches and working with multidisciplinary teams. The article concludes by making some suggestions to optimize co-impacts work, through reference to other bodies of literature. The authors highlight that this article is situated within a dominant approach to climate mitigation policy work in developing countries, which implicitly places the non-climate benefits of any action as secondary to the primary benefit of climate change mitigation and constructs an artificial separation of policy formulation and implementation. Practitioners are encouraged to reflect on the implications of these considerations in future efforts. Policy relevance One of the primary challenges to advancing climate mitigation policy in developing countries is that of perceived relevance: near-term development priorities are overwhelming. Identifying, understanding and engaging with the co-impacts of mitigation actions has emerged as one way of addressing this challenge. Although still at an experimental phase, experience with co-impacts analysis in the MAPS countries provides some useful lessons in how to develop this area of work.